2007
DOI: 10.1086/520081
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Compositions of the Type II Cepheids—The BL Herculis and W Virginis Variables

Abstract: Abundance analyses from high-resolution optical spectra are presented for 19 type II Cepheids in the Galactic field. The sample includes both short-period ( BL Her) and long-period (W Vir) stars. This is the first extensive abundance analysis of these variables. The C, N, and O abundances with similar spreads for the BL Her and W Vir show evidence for an atmosphere contaminated with 3 process and CN-cycling products. A notable anomaly of the BL Her stars is an overabundance of Na by a factor of about 5 relativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 60 publications
(139 reference statements)
8
81
0
Order By: Relevance
“…The depletion is more severe for DD Vel as the underabundances with respect to an average thick disc star reach ≈−0.30 dex for Ti, ≈−0.45 dex for Nd and Ca, ≈−0.80 dex for Sc and ≈−0.90 dex for Y. To further support the dust-gas separation, we note that most of the individual abundances fall below those of the thick-disc reference star for the elements with 50% T c > 1400 K. Hints or even clear evidence of dust-gas separation in Type II Cepheids have already been reported for ST Pup by and for CO Pup, V1711 Sgr, MZ Cyg, and SZ Mon by Maas et al (2007). On the other hand, these authors find the signature of dust-gas separation less convincing in RX Lib and W Vir because it relies mostly on the depletion in Sc.…”
Section: Chemical Compositionsupporting
confidence: 71%
See 4 more Smart Citations
“…The depletion is more severe for DD Vel as the underabundances with respect to an average thick disc star reach ≈−0.30 dex for Ti, ≈−0.45 dex for Nd and Ca, ≈−0.80 dex for Sc and ≈−0.90 dex for Y. To further support the dust-gas separation, we note that most of the individual abundances fall below those of the thick-disc reference star for the elements with 50% T c > 1400 K. Hints or even clear evidence of dust-gas separation in Type II Cepheids have already been reported for ST Pup by and for CO Pup, V1711 Sgr, MZ Cyg, and SZ Mon by Maas et al (2007). On the other hand, these authors find the signature of dust-gas separation less convincing in RX Lib and W Vir because it relies mostly on the depletion in Sc.…”
Section: Chemical Compositionsupporting
confidence: 71%
“…As we discuss in more detail in the next paragraph, severe dust-gas separation has also been reported in most of the RV Tau stars (see Giridhar et al 2005, and references therein). Maas et al (2007) found a Type II Cepheid (CC Lyr) with an extreme dust-gas separation, which is larger than in any RV Tau star. It is important to note that all the Type II Cepheids with a signature of dust-gas separation are W Vir stars and not BL Her stars.…”
Section: Chemical Compositionmentioning
confidence: 86%
See 3 more Smart Citations